Effect of elevated carbon dioxide on plant biomass and grain protein concentration differs across bread, durum and synthetic hexaploid wheat genotypes. (May 2019) - Thompson, Michael; Gamage, Dananjali; Ratnasekera, Disna; Perera, Anton; Martin, Anke; Seneweera, Saman
Abstract: Atmospheric carbon dioxide conditions predicted for future climates cause increases in wheat biomass, but also decreases wheat grain protein concentration. We investigated the response of grain protein concentration of wheat to elevated carbon dioxide in nineteen wheat genotypes, including five tetraploid, eleven hexaploid and three synthetic hexaploid genotypes to test whether decreased grain protein is genotype dependent and whether it is caused by biomass dilution. These were grown in ambient and elevated carbon dioxide conditions simultaneously. Shoot biomass and grain samples were taken at maturity. The grain protein concentration, grain biomass, shoot biomass and harvest index were analysed for each genotype. Despite most genotypes increasing in total grain protein (g), the majority of genotypes decreased in grain protein concentration (%) under elevated carbon dioxide. Elevated carbon dioxide caused an increase in grain biomass for all genotypes and total shoot biomass for most genotypes, with harvest index increasing for all genotypes except the two synthetic hexaploids CPI133814 and CPI133811. Most of the differences between wheat types were not statistically significant, suggesting that the individual genotype of wheat plants determines the response to elevated carbon dioxide rather than the wheat type. Highlights: Genotype is a greater determining factor for grain protein concentration decline under elevated CO2 than wheat type. Most genotypes declined in grain protein concentration under elevated CO2, while increasing in total grain protein. Elevated CO2 leads to a different response of harvest index between tetraploid and synthetic hexaploid genotypes. Biomass dilution is not the sole cause of grain protein concentration decline under elevated CO2 in wheat.